If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -19 = 16 Reorder the terms: -19 + 3n = 16 Solving -19 + 3n = 16 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 3n = 16 + 19 Combine like terms: -19 + 19 = 0 0 + 3n = 16 + 19 3n = 16 + 19 Combine like terms: 16 + 19 = 35 3n = 35 Divide each side by '3'. n = 11.66666667 Simplifying n = 11.66666667
| 4(x-9)=8(x+1) | | 7+2.50x=49.50 | | 8x+8+1= | | 35/5=81/x | | 0=-16t^2+32t+6 | | 6x+1=4x+2 | | (p^5/6x)^5 | | 2(7+n)=-10 | | 7x^2+100x-24=0 | | x+7-x=-5 | | x+20=2x+80 | | 45+90x=855 | | 5x+252=14x-9 | | 30-6x=12-8x | | 6t^2=-t+2 | | 7X+3Y+36=0 | | 12m+8-5m+2+m=6(m-1) | | -4x^2+50x-150=0 | | 7x+(7x+1)+(8x+3)=180 | | 0.4x-9.5(x-1)=55 | | 6a+10a^2=0 | | 2(a-7)-3a=-17-(a-3) | | 6x^2+50x+100=0 | | 12s+9t=57 | | 4x+(12)=8 | | 3a-10=25 | | 8(-2m-7)+8(-5+m)=4m-6m | | 3z+2(6-z)=-(z-1)+1 | | 3a-10=-25 | | 28*x=(4x-2)*7 | | 5-8x+x=40 | | d(3d-15)=0 |